Solid-State and Super Solidus Liquid Phase Sintering of 4340 Steel SLM Powders Shaped by Fused Filament Fabrication - Gil-Plazas, Andres-Fernando; Rubiano-Buitrago, Julián-David; Boyacá-Mendivelso, Luis-Alejandro; Herrera-Quintero, Liz-Karen (Universidad Pedagógica y Tecnológica de Colombia, 2022)
4340 steel powders were processed with an additive manufacturing process using the FFF (Fused Filament Fabrication) technique. A composite filament was developed to print samples and study the effect of the bed and nozzle temperatures on its physical and microstructural properties. The printed samples were debinded and sintered by: Solid State (SS) at 1300 °C or SLPS (Supersolidus Liquid Phase Sintering) at 1420 °C. Metallography and scanning electron microscopy (SEM) identified the microstructure and phases. The hardness of the sintered samples was measured with the Vickers method. The SLPS process contributes to better densification and volume contraction; however, it promotes geometrical distortion of the samples compared to the SS samples. The microstructure of the sintered samples consists of ferrite situated in the original austenite grain and bainite. The sintering mechanism significantly influenced the hardness of the samples. Finally, a part was designed, printed, debinded, and sintered with the aim of studying the maximum inclination angle, the minimum vertical and horizontal holes, and the minimum vertical layer thickness, which can be obtained through the whole process.